Active microrheology using pulsed optical tweezers to probe viscoelasticity of lamin A. Issue 28 (5th July 2021) - Mukherjee, C.; Kundu, A.; Dey, R.; Banerjee, A.; Sengupta, K.
Abstract : Schematic showing measurement of the viscoelasticity of purified protein sample in vitro with the help of pulsed optical tweezers and subsequent derivation of G ′ & G ′′. Abstract : Lamins are nucleoskeletal proteins of mammalian cells that stabilize the structure and maintain the rigidity of the nucleus. These type V intermediate filament proteins which are predominantly of A and B types provide necessary tensile strength to the nucleus. Single amino acid missense mutations occurring all over the lamin A protein form a cluster of human diseases termed as laminopathies, most of which principally affect the muscle and cardiac tissues responsible for load bearing functionalities of the body. One such mutation is A350P which causes dilated cardiomyopathy in patients. It is postulated that a change from alanine to proline in the α-helical coiled-coil forming 2B rod domain of the protein might severely disrupt the propensity of the filaments to polymerise into functional higher order structures required to form a fully functional lamina with its characteristic elasticity. In this study, we have elucidated for the very first time, the application of active microrheology employing oscillating optical tweezers to investigate any alterations in the viscoelastic parameters of the mutant protein meshwork in vitro, which might translate into possible changes in nuclear plasticity. We confirmed our findings from this robust yet fast method by imaging both the wild type and mutant lamin A networks using a super resolution microscope, and observed changes in the mesh size which corroborate our measured changes in the viscoelastic parameters of the lamins. This method could thus be extended to conduct microrheological measurements on any intermediate filament protein thus bearing significant implications in laminopathies and other diseases associated with intermediate filaments.